(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2016)
Introduction: India has more new tuberculosis (TB) cases annually than any other country and contributing of about twenty percent to the global burden of TB. The objective of the present study was to understand the knowledge and awareness of TB among adult male pulmonary TB patients in a rural area of West Bengal. Methodology: The present cross-sectional study was carried out among the TB patients registered under the Revised National Tuberculosis Control Programme (RNTCP). A structured questionnaire was used for data collection. Results: The mean age of the study participants was 41.46 (14.3) years.52% of the subjects never heard of TB before diagnosis of their disease. Majorities of the participants thought that smoking and chewing tobacco was the cause of TB. With regard to the mode of spread, 21% thought that TB spread through unclean food and water followed by through sharing materials for drink (21%). Most of the participants were unaware or had no idea about the fact that transmission of TB is preventable. With regard to the occurrence of TB in life time, 64% had no idea. With regard to the curability of TB, 38% said that it is curable and majorities (60%) said don’t know, 40% subjects thought that good food and drinking water can reduce the chance of getting TB. Conclusion: This study showed that lack of knowledge and misconceptions regarding TB were widespread among the TB patients. Thus, the present study emphasizes the need for health education programmes to improve knowledge, awareness and removing misconceptions about TB. SAARC J TUBER LUNG DIS HIV/AIDS, 2015 XII (2), page: 13-19